(untitled) (Acta Scientiarum. Technology, 2016)
The caviar substitute is obtained from processed fish roe, resulting in a product similar to the authentic caviar, prepared with sturgeon roe. The objective of this study was to develop a caviar substitute from roes of rainbow trout, Oncorhynchus mykiss. Four treatments were tested and we followed the steps of saline wash, drain, immersion in saline solution containing lactic acid for pH adjustment (4.3 to 4.5), salt addition (1.5 or 3%), traditional pasteurization or fast heat treatment, cooling and storage (0 to 4Â°C). The products were subjected to the physical, chemical, microbiological and sensory analyses and showed stability and safety for consumption up to 180 days in storage under refrigeration (0 to 4Â°C). Consumers showed preference for product containing 1.5% NaCl and subjected to fast heat treatment. The results suggest that caviar substitute developed with rainbow trout roes presents potential to production. Â